Evaluation of Land Suitability for Revegetation Plants at Megawati Soekarno Putri Botanical Garden Ratatotok, Minahasa Tenggara Regency - Diane Deibij Pioh; Mukhlis; Herry Frits Pinatik (Postgraduate, University of Mataram, 2025)
This study aims to: (1) Identify suitable plants for the study site; (2) Determine the suitability of the land and factors limiting the growth of revegetation plants. The study site is the post-mining reclamation land of PT. Newmont Minahasa Raya as the Megawati Soekarno Putri Botanical Garden in Ratatotok, Southeast Minahasa, North Sulawesi. The benefits gained from efforts to preserve natural resources, particularly in the concept of environmental conservation, which is important for the continuity of the ecological system and reference. This study uses a descriptive method with a survey approach and is supported by soil analysis in the laboratory. Primary data includes vegetation data, soil and water conservation measures, topography, soil depth, surface drainage, surface rocks, rock outcrops, erosion hazards, and flood/flooding hazards. Observations and soil sampling were carried out along transects. The types of plants evaluated for suitability were mahogany, teak, sengon, mango, coconut, and clove. The data were analyzed using qualitative descriptive methods. The results of the study showed that (1) there were several types of local trees that grew naturally, which were also found in secondary forests, including: Kapur wood (Melanolepsis sp.), Ficus sp., Trema orientalis, Melinjo (Gnemo gnetum) and Nyatoh/Nantu (Palaqium sp), Cananga odorata, Koordersiodendron pinnatum, Cratoxylum sp.; (2) The suitability of the land for mahogany, teak, sengon, mango, clove, and coconut trees each has a subclass of S1 (very suitable), subclass S2eh (somewhat suitable), subclass S2rc (somewhat suitable), and subclass S2eh/rc (moderately suitable), and subclass S3eh/rc (marginally suitable) with limiting factors of erosion hazard and root medium.